Exploring Literary Journalism and the Truth in Wine - Hartsock, John C (Brazilian journalism research, 2018)
Writers of narrative literary journalism are not often aware of the reasons why they write the way they do, and they usually leave critical theory outside the door of their writing space. In this essay, a writer and scholar examines critical reasons why he made choices he did as author of the award-winning book Seasons of a Finger Lakes Winery. The essay has two parts. The first part explores how narrative literary journalism attempts to narrow the distance between the subjectivities of author, reader and protagonists when compared to more conventional models of “objective” journalism. The result is hopefully a heightened degree of psychological transport on the part of the reader because of an increased cognitive response to the perception that the account is about phenomenal actuality, and the influence of the mirror neuron in mimicking that actuality. The second part exams narrative efforts in Seasons of a Finger Lakes Winery to reveal the mystique behind wine, including its science, art, and what the author describes as mystification resulting from the metaphorical “bullshit” created by the wine snob. Os escritores do jornalismo literário narrativo nem sempre têm consciência das razões por que escolhem uma forma escrita, e geralmente deixam teorizações de fora de seu espaço de escrita. Neste ensaio, um escritor e acadêmico examina as razões críticas pelas quais fez escolhas como autor do livro premiado Seasons of a Finger Lakes Winery. O ensaio tem duas partes. A primeira explora como o jornalismo literário narrativo tenta estreitar a distância entre as subjetividades do autor, leitor e protagonistas quando comparado aos modelos mais convencionais de jornalismo “objetivo”. O resultado é – assim esperamos – um grau elevado de transporte psicológico por parte do leitor, devido a uma resposta cognitiva expandida à percepção de que o relato trata da realidade dos fenômenos e à influência do neurônio-espelho em mimetizar essa realidade. A segunda parte examina os esforços narrativos em Seasons of the Finger Lakes Winery para revelar a mística por trás do vinho, incluindo sua ciência, arte e aquilo que o autor descreve como uma mistificação resultante da “lorota” metafórica criada pelos “esnobes do vinho”. Los escritores de periodismo literario narrativo no suelen ser conscientes de las razones por las que elegen sus maneras de escribir, y en general dejan las teorías fuera de su espacio de escritura. En este ensayo, un escritor y investigador examina las razones críticas por las que tomó decisiones como autor del galardonado libro Seasons of a Finger Lakes Winery. El ensayo estructurase en dos partes. La primera explora cómo el periodismo literario narrativo intenta reducir la distancia entre las subjetividades del autor, el lector y los protagonistas en comparación con los modelos más convencionales del periodismo "objetivo". El resultado – así lo esperamos – es un mayor grado de transporte psicológico por parte del lector debido a una mejor respuesta cognitiva a la percepción de que la historia describe la realidad de los fenomenos, bien como a la influencia de la neurona espejo para imitar esa realidad. La segunda parte examina los esfuerzos narrativos en Seasons of a Finger Lakes Winery para revelar la mística detrás del vino, incluida su ciencia, el arte y aquello que el autor describe como la mistificación resultante del "disparate" metafórico creado por el snob del vino.